2019
DOI: 10.1088/1361-6439/ab5a2b
|View full text |Cite
|
Sign up to set email alerts
|

Highly sensitive ionic pressure sensor based on concave meniscus for electronic skin

Abstract: Flexible pressure sensing plays a critical role in the human–machine interaction; therefore highly sensitive pressure sensors have promising potential in such applications. Capacitive pressure sensors have inherent attributes of simple configuration and fast response time. However, the existing applications of sensors are limited by the limited sensitivity as well as complex manufacturing. Herein, a highly sensitive ionic pressure sensor with the microstructured dielectric layer has been proposed. The polycarb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 39 publications
(44 reference statements)
1
23
0
Order By: Relevance
“…To circumvent the often‐difficult processes required to fabricate molds, there has been increased interest in using readily available materials as molds, including commercially available or biological materials. [ 73,74,85,86 ] A commonly used commercial material is abrasive paper because it is cost‐effective, readily available, and can sometimes be used as a mold without the need for surfactant treatment. [ 86 ] In this process, the elastomer is simply dispersed on the paper, cured, and then demolded (Figure 4C).…”
Section: Capacitive Pressure Sensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…To circumvent the often‐difficult processes required to fabricate molds, there has been increased interest in using readily available materials as molds, including commercially available or biological materials. [ 73,74,85,86 ] A commonly used commercial material is abrasive paper because it is cost‐effective, readily available, and can sometimes be used as a mold without the need for surfactant treatment. [ 86 ] In this process, the elastomer is simply dispersed on the paper, cured, and then demolded (Figure 4C).…”
Section: Capacitive Pressure Sensorsmentioning
confidence: 99%
“…An increasingly popular approach to improve the performance of capacitive pressure sensors is to manipulate the geometry of the pressure‐sensitive materials to enhance the compressibility of the dielectric layer. [ 15,67,71–74 ] When the dielectric layer is a bulk material, the applied pressure is converted to internal stress. By adding voids in the dielectric layer through microengineering, the layer can more readily deform with applied pressure, and consequently, can compress more easily ( Figure A,B).…”
Section: Capacitive Pressure Sensorsmentioning
confidence: 99%
“…[38] Utilizing the concave meniscus of pillar tip, Su et al reported an ionic pressure sensor with a high sensitivity S ≈ 10.04 kPa −1 at P < 2 kPa (Figure 10c). [225] Before loading, the electrode contacts only the periphery of the pillar. With the pressure increases, the contact area expands, leading to the formation of more EDL capacitors and increasing capacitance.…”
Section: Structure Design For Materials Elasticity Modelmentioning
confidence: 99%
“…Copyright 2017, American Chemical Society. c) Reproduced with permission [225]. Copyright 2019, IOP Science.…”
mentioning
confidence: 99%
“…Therefore, an ionic pressure sensor based on polymer composites with ILs, possessing both the elasticity of the polymer and the electrical conduction of the ILs, has received a lot of attention from researchers [25,[27][28] . For example, a highly sensitive ionic pressure sensor with a microstructured dielectric layer with a sensitivity of 35.96 kPa -1 has been prepared by Su et al [29] . Despite the great progress in ionic pressure sensors achieved so far, the development of ionic pressure sensor are stilled limited due to complicated fabrication processes and high cost.…”
Section: Introductionmentioning
confidence: 99%